Aplicando as Propriedades dos Vetores a Problemas da Geometria Clássica - Silva Neto, Felix Ferreira da (2014)
The Cartesian geometry, also called coordinate geometry, discovered by Pierre de Fermat and René Descartes, around 1636, was of great importance in mathematics, allowing study problems of Classical Geometry by algebraic methods and conversely, interpret and solve geometrically algebraic problems. The present work aims to show the use of vectors in solving problems of at and analytical geometries. The notion of vector is essential because it allows to obtain algebraic information from geometric concepts, whereas with the use of vectors geometrical demonstrations becomes simpler. In this sense, we explore the use of properties and operations with vectors in resolutions of problems of at and analytical geometries. In representations of geometric gures and graphics we use GeoGebra program.